2022
DOI: 10.1002/aelm.202200265
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Dependent Phase Transitions in HfxZr1‐xO2 Mixed Oxides: Indications of a Proper Ferroelectric Material

Abstract: Knowledge about phase transitions in doped HfO2 and ZrO2‐based films is crucial for developing future ferroelectric devices. These devices should perform in ambient temperature ranges with no degradation of device performance. Here, the phase transition from the polar orthorhombic to the nonpolar tetragonal phase in thin films is of significant interest. Detailed electrical and structural characterization is performed on 10 nm mixed HfxZr1‐xO2 binary oxides with different ZrO2 in HfO2 and small changes in oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Based on these measurements, the extracted in-plane tensile stress decreases from 1.9 to 0.6 GPa (Figure c) with a longer ALD ozone dose time. Previous work by our group reported on the ozone dose time influence on 10 nm ZrO 2 films, but the sin 2 Ψ method was not carried out. , The 10 nm ZrO 2 thin films previously reported are measured with the sin 2 Ψ method, and the stress drops from 3.4 to 1.6 GPa with a longer ozone dose time. Here, the 10 nm ZrO 2 thin films are thinner and deposited with a different ALD tool, which might lead to a different impact of the ozone dose time on the film properties, but still, a longer ozone dose time leads to a lower in-plane tensile stress.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Based on these measurements, the extracted in-plane tensile stress decreases from 1.9 to 0.6 GPa (Figure c) with a longer ALD ozone dose time. Previous work by our group reported on the ozone dose time influence on 10 nm ZrO 2 films, but the sin 2 Ψ method was not carried out. , The 10 nm ZrO 2 thin films previously reported are measured with the sin 2 Ψ method, and the stress drops from 3.4 to 1.6 GPa with a longer ozone dose time. Here, the 10 nm ZrO 2 thin films are thinner and deposited with a different ALD tool, which might lead to a different impact of the ozone dose time on the film properties, but still, a longer ozone dose time leads to a lower in-plane tensile stress.…”
Section: Resultsmentioning
confidence: 96%
“…Previous work by our group reported on the ozone dose time influence on 10 nm ZrO 2 films, but the sin 2 Ψ method was not carried out. 25,26 The 10 nm ZrO 2 thin films previously reported are measured with the sin 2 Ψ method, and the stress drops from 3.4 to 1.6 GPa with a longer ozone dose time.…”
Section: Structural Analysis Figure 1ab Shows Gixrd Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 Indeed, it is reported that the fraction of the monoclinic phase increases for lower heating and cooling rates. 10 It is also reported 11 that stabilization of the orthorhombic phase in undoped or lightly Zr-doped HfO 2 films requires a high quench rate, while the effect of the quench rate is less relevant for higher dopant concentration. On the other hand, kinetics also conditions the transformation between the tetragonal and orthorhombic phases since the orthorhombic phase has lower energy than the tetragonal phase at room temperature but not at high temperatures.…”
Section: Introductionmentioning
confidence: 96%
“…[19][20][21][22][23][24][25] The first-order nature of the phase transition is predicted by Landau theory and supported by experimental observations of temperatureinduced phase transitions of the ferroelectric o-phase to the nonpolar t-phase. [18,26,27] The electric field-induced phase transitions generating AFE behavior, however, have remained hidden from view despite theoretical and supporting experimental evidence. Direct physical observations are needed for greater exploitation of this nonlinear phenomenon to pave the way for next-generation steep-slope transistors, antiferroelectric-based memories, supercapacitors, neuromorphic devices, and transducers.…”
Section: Introductionmentioning
confidence: 99%